Long-term surface ozone variability at Mt. Cimone WMO/GAW global station (2165 m a.s.l., Italy). (January 2015) - Cristofanelli, P.; Scheel, H.-E.; Steinbacher, M.; Saliba, M.; Azzopardi, F.; Ellul, R.; Fröhlich, M.; Tositti, L.; Brattich, E.; Maione, M.; Calzolari, F.; Duchi, R.; et al.
Abstract: The Mediterranean basin represents a hot spot area for short-term O3 distribution and anthropogenic contributions to it. This is why we analysed in this work the surface O3 variability observed at Mt. Cimone WMO/GAW global station (CMN, 44°12′ N, 10°42′ E, 2165 m a.s.l., Italy) from 1991 to 2011. The measurements performed at this mountain observatory represent the longest surface O3 record at a baseline site in the Mediterranean basin. Monthly O3 averages at CMN show a typical seasonal cycle characterised by a winter minimum and a spring – summer maxima. The shape of the mean annual variation of O3 is well comparable with those observed at other four baseline sites in the Alps and in the Mediterranean region: Jungfraujoch – Swiss Alps, Sonnblick – Austrian Alps, Mt. Krvavec– Slovenia and Giordan Lightouse – Island of Gozo, Malta. In general, O3 levels at CMN show higher values during warm months, which is likely to be related both to vertical transport of polluted air-masses at regional and continental scales and to enhanced photochemistry. Here, we also investigate the influence of specific atmospheric processes (i.e. the occurrence of heat-waves, North Atlantic Oscillation, thermal transport of air-masses from the regional PBL and stratospheric intrusions) in affecting O3 variability at CMN. Overall, a significant positive (95% confidence level) linear trend in monthly O3 mole fraction was observed over the period 1991–2011 (0.21 ± 0.10 nmol/mol yr −1 ) while no trend (-0.02 ± 0.12 nmol/mol yr −1 ) was detected for the 1996–2011, when measurements were carried out by an homogeneous experimental set-up. On a seasonal basis, a positive trend has been observed for 1996–2011 (0.34 ± 0.32 nmol/mol yr −1 ) only for spring. Significant decreases of the seasonal O3 growth-rates have been detected at CMN during 1991–2011 from winter to spring and only for summer during 1996–2011. Highlights: We analysed 19 years of surface O3 data at the Mt. Cimone station (2165 m, Italy). High O3 values were observed during summer in the Mediterranean region. NAO variability appeared to affect winter O3, while heat-waves affected summer O3 . O3 increased over 1991–2011 but no trends were detected for the 1996–2011. Summer O3 growth-rates showed a slowing-down in recent years.